Pengaruh Model Pembelajaran Koooperatif Tipe Student Teams Achievement Divisions Terhadap Kemampuan Komunikasi Matematis Peserta Didik Kelas VIII SMPN 5 Kota Solok - ANNISA GUSTI FAJRIAH (Jurnal Edukasi dan Penelitian Matematika, 2020)
The mathematical communication skill is an important aspect and should be achieved in the learning of mathematics. The Importance of mathematical communication skill for students make this capability need to be improved in the learning process of mathematics. The observation results indicate that the mathematical communication skill of the students in SMPN 5 Kota Solok was still low. The method that can be applied to improve the mathematical communication skill of students is by applying cooperative learning Student Teams Achievement Divisions model. The type of research was quasy-experimental and descriptive with the randomized control group only design. The results of this research showed that  the development of mathematical communication skill of students whose during learning process using STAD model has increased, and mathematical communication skill of students whose learning process using STAD model is better than mathematical communication skill of students whose learning with direct learning.Keywords – Mathematical Communication Skill, Cooperative Learning Model, Student Teams Achievement Divisions.